Serving the south: television infrastructures and the development of regionality during the emergence of ITV - Groom, Elinor (2016)
This thesis analyses the early infrastructural development of Southern Television, the now-defunct franchise company that was created in 1958 to serve the South of England on behalf of Independent Television (ITV). In particular, it identifies how Southern Television's status as a regional broadcaster affected the implementation and development of its policies, regulations, resources and practices from the late 1950s to the late 1960s. Histories of regional broadcasting have heretofore focused on programmes that evoke regional culture, and more often than not these histories have ignored the South in favour of northern cultures. This thesis approaches the history of regional broadcasting from a different perspective, one that considers where the region was visible in the internal workings of a regional broadcaster, as opposed to identifying the region in that broadcaster's output.